ANALISIS DEBIT AIR DAN MUATAN SUSPENSI PADA DAS DUA LAUT TANAH BUMBU KALIMANTAN SELATAN - Andi Ilyasa; Syarifuddin Kadir; Rina Kanti (Universitas Lambung Mangkurat, 2020)
This research aims to analyze the amount of water discharge and the content of suspension load in the DAS Dua Laut Tanah Bumbu of South Kalimantan, to analyze the relationship between water discharge and suspension load in the DAS Dua Laut Tanah Bumbu of South Kalimantan. This research was carried out in December 2017 to March 2018. The reseach location was in Biduri Bersujud Village for the upstream and in Damar Indah Village for the downstream. The average downstream discharge is 0.953 m3/second, a minimum of 0.020 m3/second, and a maximum of 13.590 m3/second. The downstream debit is an average of 2.12 m3/second, a minimum of 1.19 m3/second and the maximum is 6.25 m3/second. The upstream suspension content was 0.01 g/l, the average upstream suspension discharge was 0.0001 tons/day, the downstream supply load was 0.1 g/l, the average downstream suspension discharge was 0.0015 tons/day. The upstream determination (R²) is 0.992 from varabel y = 0.0009x0.9931 and the determination (R²) downstream is 1 from the variable y = 0.0009x0.9999.Keywords: water discharge; Suspension; Regression diagram